2021
DOI: 10.1039/d1ra00088h
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic alloy for high-efficiency photovoltaic conversion in solar cells: first-principles insights when doping SnO2 rutile with coupled Eu–Gd

Abstract: A material design of half-metallic ferromagnetic semiconductors based on (Eu, Gd)-doped SnO2 rutile is proposed for High-Efficiency Photovoltaic Conversion in solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The high value of the absorption coefficient in the ultraviolet region contributes to an extremely efficient photon conversion process, which means that a quantum cut may be observed in the systems co-doped with transition metals. 17,54,55 This result provides a new idea for developing and using SnO 2 -based optics.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The high value of the absorption coefficient in the ultraviolet region contributes to an extremely efficient photon conversion process, which means that a quantum cut may be observed in the systems co-doped with transition metals. 17,54,55 This result provides a new idea for developing and using SnO 2 -based optics.…”
Section: Resultsmentioning
confidence: 86%
“…SnO 2 co-doped with rare earth elements (Eu, Gd) demonstrates that this ferromagnetic alloy can absorb up to 96% in the visible light range and it can convert heat energy into electricity efficiently at room temperature. 17 The efficiency of a thermoelectric material in converting heat into electrical energy is dened by the gure of merit, where S is the Seebeck coefficient, s the electrical conductivity, K the total thermal conductivity and T the absolute temperature. [18][19][20][21][22][23][24][25][26] The charge carrier concentration and mobility control both the Seebeck coefficient and the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have used spin-polarized calculations to provide a comprehensive assessment of the electronic structures of the range of investigated perovskites, characterize their magnetic properties, and evaluate their capacity to be applied in PSCs and Per-SCs. Since ferromagnetic materials have shown significant potential to absorb a meaningful amount of visible light, their integration into solar cells may improve the efficiency of these devices [41].…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 99%
“…Perovskite oxides with wide band gaps exceeding 2 eV have been utilized as CTLs and TCE in solar cells [29][30][31][32][33][34][35], whereas metallic compounds are widely utilized in PSCs and Per-SCs, for example, as absorbents in the active layer [36][37][38][39][40]. Research has also indicated that the utilization of magnetic materials as absorbents in the active layer of solar cells could potentially enhance their performance [41].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, co-doping or double doping seems to be required for tuning the materials' properties. Saadeddin et al [18] found that the double doping of SnO 2 by Zn and Sb significantly improved its electrical conductivity and density, and the presence of Zn prevents the Sb evaporation during solid-state reaction at 1300 • C. According to Lamrani [19], the double (Eu, Gd) impurities substitute the adjacent Sn sites and result in strong ferromagnetic interactions via the p-f hybridization between rare-earth 4f and Op states. The obtained ferromagnetic alloy is expected to act as a great power source for effective photovoltaic conversion in solar cell applications.…”
Section: Introductionmentioning
confidence: 99%